2014
DOI: 10.1007/s13149-014-0397-y
|View full text |Cite
|
Sign up to set email alerts
|

Vieillissement et pathologies chroniques au Sénégal. Comparaison entre des populations vivant en milieu rural (Ferlo) et urbain (Dakar)

Abstract: The objectives of this study were: to compare the prevalence of hypertension, overweight and obesity in rural (Ferlo) and urban (Dakar) Senegalese populations aged 50 and over. The survey was conducted on individuals aged 50 and older living in the rural area (N=478) and in the urban area (N=220). We have collected data about age, gender, marital status, education level, and knowledge, treatment of hypertension, height, weight and blood pressure. We have observed that overweight and obesity were more prevalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
2
6
1
Order By: Relevance
“…Of the 34 included studies, five [42, 44–46, 56] did not provide information on how blood pressure was measured. Studies that did, only provided scant information which showed differences in the protocol in terms of the number of visits at which blood pressure was measured, frequency of measurements per visit, the readings used in the analysis, the posture of the subject and the part of the body on which measurements were taken (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 34 included studies, five [42, 44–46, 56] did not provide information on how blood pressure was measured. Studies that did, only provided scant information which showed differences in the protocol in terms of the number of visits at which blood pressure was measured, frequency of measurements per visit, the readings used in the analysis, the posture of the subject and the part of the body on which measurements were taken (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Using the Hoy tool [30], we determined that eight studies had a high risk of biased estimate [44, 46, 51, 52, 54, 62, 65, 66] and nine studies [40, 47, 53, 56, 57, 61, 67, 69, 70] had a moderate-risk of bias while the remaining 17 studies had low risk of bias (S5 Table). The pooled prevalence of hypertension did not differ by the study’s evaluated risk of bias (S2 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Residence In studies in which the residential distribution of the prevalence of hypertension was reported, it was higher in urban than in rural areas by up to 15 percentage points [22, 24, 31, 36, 43]. In one study in Nigeria, the prevalence increased along a gradient from rural, semi-urban to urban areas [37].…”
Section: Resultsmentioning
confidence: 99%
“…7,19,20 The study found no rural–urban associations for arthritis, asthma, lung disease, low vision, stroke and/or angina and hypertension, while previous studies found an association between urban residence and asthma morbidity, 15,16 chronic lung disease, 16 stroke, 16 angina 16 and hypertension. 16,17…”
Section: Discussionmentioning
confidence: 99%
“…Among older adults, urban residence has been found to be associated with a higher prevalence of asthma morbidity, 15 chronic lung disease, 16 stroke, 17 angina, 16 hypertension 16,17 and diabetes. 7,15,16,18 Several studies found a higher prevalence of underweight or malnutrished among rural people rather than urban older adults.…”
Section: Introductionmentioning
confidence: 99%